Pelaksanaan Bimbel Gratis Guna Meningkatkan Pemahaman Materi Anak Sekolah Dasar di RW 02 Kelurahan Jelekong, Kecamatan Baleendah, Kabupaten Bandung - ali, fadilah inayat ali; Febriani, Riska Febriani; Oktaviani, Salsabila Oktaviani (PROCEEDINGS UIN SUNAN GUNUNG DJATI BANDUNG, 2024)
Education is an important thing in the development and progress of the nation and state. Sometimes we as individuals must be aware of the things around us. There are still many people who think that education is just a bond that can only be accessed by lucky people. Therefore, we created a Free Tutoring program for all subjects. It is solely to help balance education, especially RW 02, Jelekong Village, Baleendah District, Bandung. This activity aims to improve the understanding of elementary school children’s material through a free tutoring program. This program is implemented by us, KKN students and collaborates with local youth organizations in terms of teaching. This activity also involves parents, local government, and the community of RW 02, Jelekong Village to increase awareness and participation in education.